Worst-Case Robust Training Design for Correlated MIMO Channels in the Presence of Colored Interference - Jae-Mo Kang; Sangseok Yun (Mathematics, 2025)
The covariance information at the transmitter side is often subject to mismatches due to various impairments. This paper considers a training design problem for multiple-input multiple-output (MIMO) systems when both channel and interference covariance matrices are imperfect at the transmitter side. We first derive the structure of the optimal training signal, minimizing the worst-case mean square error (MSE). With the training structure, the original problem becomes a simple power allocation problem. We propose a numerical optimal power allocation scheme and a closed-form suboptimal power allocation scheme. Simulation results show that the proposed schemes considerably outperform the conventional schemes in terms of the worst-case MSE and bit error rate (BER) performances, and the proposed closed-form training scheme has comparable performance to that of the optimal one. For example, the proposed schemes yield more than 2.5 dB signal-to-interference ratio (SIR) gains at a BER of <semantics>10−4</semantics>.